Perancangan Masjid Di Pekanbaru Dengan Pendekatan Arsitektur Futuristik - Alisha Safira Matroni; Muhd Arief Al Husaini; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Pekanbaru City is the capital city of Riau province, where the majority of the population is Muslim. Therefore, the existence of a representative mosque as the main means of worship for Muslims is very necessary. In general, the number of mosques in Pekanbaru City is sufficient, this is proven by the fact that it is not difficult for immigrants to find mosques when they are going to worship. However, the existence of the existing mosque building is still seen as not being able to represent the vision of the city of Pekanbaru "The Realization of Pekanbaru as a Smart City Madani", where one of the missions is to Increase Human Resources (HR) who are Faithful, Independent, Resilient and Highly Competitive. To realize a place of worship or a mosque that fulfills the mission of the city of Pekanbaru, a mosque is designed with a futuristic architect approach. Futuristic architecture is an understanding of freedom in expressing or expressing ideas or ideas into an unusual, creative and innovative display form. The design of a mosque with a futuristic architectural concept related to technology requires a special design that refers to space requirements, the appearance of the building and the use of materials with today's technology. The construction of this mosque is expected to become an icon of Pekanbaru City to support the vision of the city that has been set by the Mayor of Pekanbaru.Keywords: Futuristic Architecture, Mosque, Pekanbaru City